The implementation of grammatical functions in Functional Discourse Grammar - Bakker, Dik; Siewierska, Anna (UNESP, 2009)
In standard FG (DIK, 1997) grammatical functions are assigned directly to the underlying representation in a more or less across the board fashion, only taking into consideration the language dependent semantic function hierarchy. This approach bypasses a number of constraints on subject assignment that may be gathered from typological data, and observed from the actual behaviour of speakers. In this contribution, we make an attempt to reinterpret FG syntactic functions in the light of the FDG model. Following ideas from Givón (1997), we propose a treatment of Subject assignment on the basis of a combination of semantic and pragmatic factors of the relevant referents and other functional aspects of underlying representations. The assignment rules adhere to the respective hierarchies as discussed in the typological literature. In our proposal, Subject (and Object) assignment are now located in the expression component, more specifically in the dynamic version of the expression rules as proposed in Bakker (2001).